Actinopyga spinea Cherbonnier, 1980 (Holothuroidea: Holothuriida:Holothuriidae), new addition to the holothuroid fauna of Pakistan - Ali, Qadeer Mohammed; Shaikh, Iqra; Thandar, Ahmed; Ahmed, Quratulan (Zootaxa, 2024)
We here in report on the first record of Actinopyga spinea from the intertidal zone from Balochistan, Pakistan in the northern Arabian Sea. Its taxonomic characters, habitat and distribution are described.